2015
DOI: 10.1111/cbdd.12659
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of In vitro PDT Activities and In vivo Biopotential of Zinc Phthalocyanines Using 131I Radioisotope

Abstract: Novel octylthio-containing asymmetrically substituted Zn(II) phthalocyanine (Zn(II)Pc1) and a symmetric derivative (Zn(II)Pc2) have been prepared to investigate the biological potential and ability to photosensitize singlet oxygen for photodynamic therapy applications. In this study, the singlet oxygen generation potential and in vitro photodynamic activities of these compounds have been tested. Both ZnPcs reveal to be very efficient singlet oxygen generators and promising PSs for PDT applications. In vitro PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The effect of non-liposomal AlPc and ZnPc was not reported in these studies. PDT efficacy of the symmetric derivative Zn(II)Pc 1 and asymmetrically substituted ZnPc(II) 2 have been investigated in mouse mammary carcinoma EMT6/P cells and HeLa cervical adenocarcinoma cells [ 49 , 50 ]. Zn(II)Pc 1 was photocytotoxic in EMT6/P cells (IC 50 ~3.14 μM) but not in HeLa cells, whereas Zn(II)Pc 2 was not phototoxic in EMT6/P cells but was photoactive in HeLa cells (IC 50 ~3.13 μM at 30 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of non-liposomal AlPc and ZnPc was not reported in these studies. PDT efficacy of the symmetric derivative Zn(II)Pc 1 and asymmetrically substituted ZnPc(II) 2 have been investigated in mouse mammary carcinoma EMT6/P cells and HeLa cervical adenocarcinoma cells [ 49 , 50 ]. Zn(II)Pc 1 was photocytotoxic in EMT6/P cells (IC 50 ~3.14 μM) but not in HeLa cells, whereas Zn(II)Pc 2 was not phototoxic in EMT6/P cells but was photoactive in HeLa cells (IC 50 ~3.13 μM at 30 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The photodynamic therapy efficacies of ZnPc, ZnPc‐TiO 2 , and TiO 2 have been evaluated in control group that non‐cytotoxicity at concentrations of 1.57, 3.13, and 6.25 μ m without phototherapy (PT‐). The phototoxicities of ZnPc, ZnPc‐TiO 2 , and TiO 2 were determined according to the untreated control group in which the substance was not applied and the light was applied …”
Section: Methodsmentioning
confidence: 99%
“…Biodistribution studies revealed that radiolabeled Zn(II)Pc1 showed significant uptake in the brain, intestine, pancreas and ovary. Hence, these Pcs derivatives could also be promising candidates for the nuclear imaging of tumors [ 109 ].…”
Section: A Review Of the Literaturementioning
confidence: 99%